2019
DOI: 10.1111/jocd.12952
|View full text |Cite
|
Sign up to set email alerts
|

Open‐label study assessing the efficacy and tolerability of topical skin care and sun protection alone and in combination with intense pulsed light therapy

Abstract: Background Intense pulsed light therapy (IPL) decreases facial erythema and telangiectasias associated with rosacea. Topical skin care products decrease facial erythema by the action of active ingredients and masking effects. Objectives To assess the efficacy and tolerability of combining a topical skin care regimen (TSCR) comprised of a multifunctional three‐in‐one facial cream and a mineral‐based brush‐on SPF50 powder sunscreen with a single IPL treatment for treating mild‐to‐severe facial redness associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A retrospective study including 31 subjects revealed that the combination of pulsed dye laser and 1.0% oxymetazoline cream reduced erythema and telangiectasias both safely and effectively [55]. An open-label study including 21 subjects assessed the efficacy and tolerability of topical skin care and sun protection combined with IPL therapy [56]. After using a topical skin care regimen (TSCR) monotherapy for 12 weeks, subjects received a single IPL light therapy, following which they continued the TSCR monotherapy for another 6 weeks.…”
Section: Laser-and Light-based Therapiesmentioning
confidence: 99%
“…A retrospective study including 31 subjects revealed that the combination of pulsed dye laser and 1.0% oxymetazoline cream reduced erythema and telangiectasias both safely and effectively [55]. An open-label study including 21 subjects assessed the efficacy and tolerability of topical skin care and sun protection combined with IPL therapy [56]. After using a topical skin care regimen (TSCR) monotherapy for 12 weeks, subjects received a single IPL light therapy, following which they continued the TSCR monotherapy for another 6 weeks.…”
Section: Laser-and Light-based Therapiesmentioning
confidence: 99%
“…Previous studies in patients with rosacea and those with facial photodamage have demonstrated that a topical skin care regimen in combination with IPL results in a greater improvement in overall facial redness than IPL alone. 20,21 When the epidermal barrier is disrupted as in rosacea, there is an increase in trans-epidermal water loss with a subsequent reduction in epidermal hydration levels, triggering inflammation. 22 Appropriate skin care formulations that increase hydration levels may reduce the damage to the stratum corneum, thereby maintaining the epidermal barrier function and reducing skin irritation.…”
Section: Discussionmentioning
confidence: 99%
“…Several other combinations of topical and energy‐based therapies have also shown potential in reducing symptoms associated with rosacea. In an open‐label study, the treatment effects of a skin care regimen consisting of a 3‐in‐1 facial cream and SPF 50 mineral sunscreen powder in combination with IPL were investigated [18]. Patients with rosacea applied the skin care regimen daily for 18 weeks and received a single IPL treatment at week 12.…”
Section: Discussionmentioning
confidence: 99%